Core-shell ZrC/Ti2AlC reinforced composite coatings prepared by laser cladding on Zr-alloy substrates. Issue 6 (15th March 2022) - Xiao, Yi; Xiao, Huaqiang; Feng, Jinyu; Lin, Bo; Wang, Ying
Abstract: Core-shell ZrC/Ti2 AlC reinforced intermetallic composite coatings were successfully prepared by laser cladding in-situ reaction using TiAl–TiC–Al powder preset on R60702 zirconium alloy surface. As-obtained coatings showed good metallurgical bonding with substrates. Composite coatings mainly contained dendritic ZrC/Ti2 AlC reinforced phase with core-shell structure and intermetallic matrix of Ti x Al y and Zr x Al y, with small amounts of Ti3 AlC. During laser pool solidification, TiC nucleated at boundary of primary precipitated ZrC dendrite. Al atoms then diffused into TiC outer layer during subsequent solidification process to finally form core-shell structure with ZrC as core and Ti2 AlC as outer layer. Ti2 AlC phase of shell structure improved physical performance between hard ZrC particles and matrix in terms of hardness and thermal expansion coefficient. The maximum hardness of cladding layer (848.8 HV) was 5-fold higher than that of zirconium alloy substrate. Also, no cracking was found inside the coatings or at the junction with substrates. In sum, these findings look promising for future applications of MAX phase composite coatings in nuclear power equipment.